Consumption Smoothing in the Demand for Health Care - Nicolai Kristensen; Henrik Lindegaard Andersen (Institute for the Study of Labor (IZA), 2016)
We investigate how, in temporary economic hardship, agents change their consumption of health services, and how this depends on whether the service is universally free-of-charge visits to GP's or privately co-financed dental care. We find that own expenditures for dental care decrease. The decrease is mainly seen in preventive treatment, a durable good, but for the lowest income quartile there is also a substantial decrease in expenditures for curative dental care, although this is a consumption good with very low intertemporal substitution. The expenditures for GPs are unaltered. The findings indicate that consumption of health services critically depends on the existence of user charges versus universal coverage. The welfare loss associated with postponement of preventive care is considerably lower than the welfare loss related to a decrease in the use of curative dental care induced by economic hardship. The policy implication could be public support for means-tested curative dental services.
Keywords: D1; D6; H23; 330; health care systems; consumption smoothing; social gradient